2016
DOI: 10.1186/s40337-016-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

Chew and Spit (CHSP): a systematic review

Abstract: BackgroundThis systematic review is an evaluation of the empirical literature relating to the disordered eating behaviour Chew and Spit (CHSP). Current theories postulate that CHSP is a symptom exhibited by individuals with recurrent binge eating and Bulimia Nervosa.AimsThe review aimed to identify and critically assess studies that have examined the distribution of CHSP behaviour, its relationship to eating disorders, its physical and psychosocial consequences and treatment.MethodsA systematic database search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…In the present study, CHSP occurred in older individuals compared with that reported in our systematic review (M 5 24, SD 5 8) (Aouad et al, 2016). Differences are between individuals (male and female) that engage in CHSP (regardless of clinically diagnosable ED) and people from the HOS 2,016 representative sample (general population)-using unweighted data for CHSP.…”
Section: Discussionmentioning
confidence: 39%
See 4 more Smart Citations
“…In the present study, CHSP occurred in older individuals compared with that reported in our systematic review (M 5 24, SD 5 8) (Aouad et al, 2016). Differences are between individuals (male and female) that engage in CHSP (regardless of clinically diagnosable ED) and people from the HOS 2,016 representative sample (general population)-using unweighted data for CHSP.…”
Section: Discussionmentioning
confidence: 39%
“…This may be due to the younger ED samples used for studies identified in the review (Aouad et al, 2016;Guarda et al, 2004;Song, Lee, & Jung, 2015). Nonetheless, as older women are less likely to admit to, and seek treatment for, ED behaviors than younger counterparts, it may be speculated that CHSP behaviors were under-reported in the general population (Aouad et al, 2016;Guarda et al, 2004;Song et al, 2015). However, in our systematic review those with CHSP were younger than the general population (Median CHSP 5 39 vs.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations